GETAH JELUTUNG SEBAGAI HASIL HUTAN BUKAN KAYU UNGGULAN DI LAHAN GAMBUT - Marinus Kristiadi Harun (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2015)
Public preference for the jelutung as a species for forest and land rehabilitation is currently increasing. The aim of this research is to identify and analyze jelutung's latex as a leading non timber forest products (NTFP). Jelutung's latex as a leading NTFP be analyzed using the criteria and indicators stated in Forestry Minister Decree No. P.21/Menhut-II/2009, that includes economic aspect, biophysical and environmental, institutional, social and technological aspects. In the economic aspect, the parameters under study include marketing margins of jelutung's latex and financial analysis of developed jelutung's latex with agroforestry systems. This study was conduct by focus group discussion (FGD) and interview method. The analysis results on the social aspect show that jelutung's latex is categorized as a provincial superior NTFP with superior total value (STV) of 72.62. The economic aspect shows that the marketing margin of jelutung latex is still inefficient as its value is >50%. The financial analysis results show that jelutung forest is feasible to be developed both in the monocultural and agroforestry patterns. NPV, BCR and IRR of jelutung with agroforestry pattern are IDR 69,799,338, 8.68 and 29% respectively. Institutional system proposed to overcome the existing obstacles is colaborative economics system (CES).